Effects of Emotional-Focused Therapy on the Management of Emotional Health Problems of Teachers in Ilorin Metropolis - Lasisi, Adekola Kamil; Annor, Patricia Omioguele (Educational Psychology Journal, 2023)
The level of the emotional health of teacher has been noticed to be on the high side and this affects their performances. This study investigated the effects of emotionally focused therapy on the management of emotional health problems of teachers in Ilorin metropolis. The research design used was quasi-experimental. An experimental design of 2 by 2 factorial matrix which adopts pre-test and post-test treatment was employed in this study. All secondary school teachers in Ilorin metropolis constituted the population for the study while selected secondary school teachers experiencing emotional health problems were the target population for this study. 30 secondary school teachers experiencing mental health problems were sampled for this study. An Emotional Health Problems Scale (EHPS) designed by Warwick-Edinburgh was adopted for this study. Analysis of Covariance (ANCOVA) was the major statistical tool that was employed to test seven hypotheses generated at 0.05 level of significance. The result of the findings revealed that emotional-focused therapy is effective in managing the emotional health problems of teachers in Ilorin metropolis. There were no significant main effects of age or gender on the emotional health of secondary school teachers in Ilorin metropolis. It was also revealed that there were no significant interactive effects of age or gender on the emotional health of secondary school teachers in Ilorin metropolis but significant interactive effects were found on treatment, age and gender on the emotional health of secondary school teachers in Ilorin metropolis. It was recommended that mental health professionals should consider EFT as a valuable therapeutic option for teachers experiencing emotional difficulties. Therapists should consider these demographic factors when implementing EFT and be prepared to adapt their approach accordingly.